RELATIONSHIP BETWEEN THE KYRGYZ AND MONGOLS IN THE ERA OF CHINGGIS KHAN AND HIS DESCENDANTS IN THE 13TH CENTURY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This research is dedicated to a comprehensive analysis of the relationship between the Kyrgyz and the Mongol Empire in the 13th century. Based on a critical analysis of a wide range of historical sources, including the “Secret History of the Mongols,” Rashid al-Din’s work “Jami’ al-Tawarikh,” and 15th-century documents, the study explores the military-political, social, and ethno-cultural aspects of the interaction between the two peoples. Special attention is given to investigating the contradictory accounts of the nature of Kyrgyz tribes’ resistance to Mongol expansion. The study demonstrates the long-term impact of the Mongol conquest on the transformation of social structure, political institutions, and ethnic identity of the Kyrgyz people, making a significant contribution to the understanding of the processes of ethnogenesis and state-building in Central Asia.
Keywords: Kyrgyz, Mongol conquests, Central Asia, 13th century, Secret History of the Mongols, Jami’ al-Tawarikh, Rashid al-Din, military resistance, ethnic development